Strategy for Utilizing TikTok Videos as a Digital Promotion Tool to Increase Market Reach for MSME Pondok Tamia : Strategi Pemanfaatan Video TikTok sebagai Media Promosi Digital dalam Meningkatkan Jangkauan Pasar UMKM Pondok Tamia - Maulitna Anjiliani; Dwi Nur Farida; Depita Sebtiani; Agus Dwi Cahya (Institut Riset dan Publikasi Indonesia, 2026)
The majority of food-related SMEs in Indonesia have not yet fully leveraged short-form video platforms like TikTok as a digital promotional tool. This community service project aims to assist SMEs in Pondok Tamia, Yogyakarta, in designing and implementing a TikTok-based promotional strategy to enhance brand visibility and market reach. The approach used was participatory action research (PAR) with three stages: identifying partners through surveys and semi-structured interviews, designing a content strategy, and producing and publishing three TikTok videos over approximately one month. Participants in the activity consisted of three students and one lecturer from the Management Study Program at Sarjanawiyata Tamansiswa University, Yogyakarta. Evaluation was conducted through analysis of content performance data (views, likes, comments, and shares) as well as observation of changes in partners’ understanding. The results of the activity showed a significant increase in all indicators, with the total views of the three TikTok content videos reaching 13.089 and likes totaling 250. The partners’ understanding of digital marketing also improved, as evidenced by their ability to manage their TikTok accounts independently following the mentoring. The novelty of this activity lies in the integration of Ki Hajar Dewantara’s philosophical values (Ngandel, Kendel, Kandel, Bandel) as the foundation for SME digital entrepreneurship. These findings confirm that a well-planned TikTok content strategy is an effective and sustainable digital promotion solution.